THE INFLUENCE OF PROFITABILITY, SOLVENCY, BANKRUPTCY PREDICTION, AND OPERATIONAL COMPLEXITY ON AUDIT REPORT LAG (Empirical Study on Mining Sector Companies Listed on the Indonesia Stock Exchange in 2021–2023) - Ni Luh Putu Kaila Shiva Karang; I Ketut Sujana (CV. Adiba Aisha Amira, 2025)
The annual financial report plays a crucial role in providing financial information to stakeholders and must be audited to ensure its reliability and compliance with regulations. Timeliness in the submission of financial statements is considered a key indicator reflecting the quality, reliability, and transparency of financial information. Audit report lag refers to the time period required to complete the audit process. The longer it takes for the auditor to complete their audit work, the greater the risk of delayed financial reporting, which can be detrimental to the company. This study aims to empirically examine the influence of profitability, solvency, bankruptcy prediction, and operational complexity on audit report lag. The research was conducted on mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 37 companies with a total of 95 observations. Data were analyzed using multiple linear regression. The findings indicate that profitability has a negative effect on audit report lag, while solvency has a positive effect. However, bankruptcy prediction and operational complexity do not have a significant effect on audit report lag.